2017
DOI: 10.1016/j.jtho.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ctDNA Analysis for Detection of the EGFR  T790M Mutation in Patients with Advanced Non–Small Cell Lung Cancer

Abstract: The cobas plasma test detected the T790M mutation in 61% of tumor tissue T790M mutation-positive patients. To mitigate the risk of false-negative plasma results, patients with a negative plasma result should undergo a tissue test where feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
194
8
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(213 citation statements)
references
References 33 publications
8
194
8
3
Order By: Relevance
“…Finally, 40% of patients with a mNSCLC diagnosis are eligible to receive the second-line treatment [3]; of them, 82% are eligible for the tissue re-biopsy [5] and 100% for the liquid one. Table II shows the percentages of sensitivity and specificity associated with the COBAS ® test performed on tissue (tissue biopsy) or plasma (liquid biopsy) samples and considered here [17,18]. In addition to these data, in the model -based on what is indicated in the literature -in the presence of a tissue biopsy, a 14% probability that the diagnostic investigation could determine the onset of a post-procedure complication (eg.…”
Section: Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 40% of patients with a mNSCLC diagnosis are eligible to receive the second-line treatment [3]; of them, 82% are eligible for the tissue re-biopsy [5] and 100% for the liquid one. Table II shows the percentages of sensitivity and specificity associated with the COBAS ® test performed on tissue (tissue biopsy) or plasma (liquid biopsy) samples and considered here [17,18]. In addition to these data, in the model -based on what is indicated in the literature -in the presence of a tissue biopsy, a 14% probability that the diagnostic investigation could determine the onset of a post-procedure complication (eg.…”
Section: Populationmentioning
confidence: 99%
“…Patients eligible for the second-line treatment (40.0%) 6,890 [3] Patients eligible for the tissue re-biopsy (82.0%) 5,650 [5] Patients eligible for the liquid biopsy (100.0%) 6,890 Assumption [17,18] determining the presence of DNA mutations, only the sampling of venous blood is provided for. Every single specialist outpatient service was then attributed a value, considering the respective fee refunded by the NHS [20].…”
Section: Second-line Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has demonstrated the feasibility of using “hotspot” and comprehensive cfDNA profiling for identification of activating mutations and therapeutic resistance mechanisms in EGFR -mutated NSCLC. 1824 However, its utility in evaluating ALK gene fusions has not been assessed on a large scale. Small studies, such as a recent report that identified two cfDNA ALK fusions in a cohort of 102 patients show that the detection of these alterations is feasible, albeit more technically challenging than somatic mutation detection, while a longitudinal evaluation of 22 patients was able to detect ALK fusions in 86% at progression.…”
Section: Introductionmentioning
confidence: 99%
“…AURA extension and AURA2 phase II studies using COBAS RT platform have reported overall predictive agreement of T790M reported in tumor tissue and plasma samples to be 65%. [41] Ahsan et al . have reported concordance of around 77% on DdPCR for T790M.…”
Section: Discussionmentioning
confidence: 99%